Spectral K-edge subtraction imaging of experimental non-radioactive barium uptake in bone. Issue 12 (December 2016) - Panahifar, Arash; Samadi, Nazanin; Swanston, Treena M.; Chapman, L. Dean; Cooper, David M.L.
Graphical abstract: Highlights: The spectral K-edge subtraction (SKES) method successfully detected barium in bone. The SKES method is less susceptible to 'crossover' artifact than conventional method. Barium at low doses could be used as an experimental tracer of bone turnover. Barium predominately incorporated in the bone being formed during its administration. Low doses of barium did not cause any toxicological manifestation. Abstract: Purpose: To evaluate the feasibility of using non-radioactive barium as a bone tracer for detection with synchrotron spectral K-edge subtraction (SKES) technique. Methods: Male rats of 1-month old ( i.e., developing skeleton) and 8-month old ( i.e., skeletally mature) were orally dosed with low dose of barium chloride (33 mg/kg/day Ba 2+ ) for 4 weeks. The fore and hind limbs were dissected for imaging in projection and computed tomography modes at 100 μm and 52 μm pixel sizes. The SKES method utilizes a single bent Laue monochromator to prepare a 550 eV energy spectrum to encompass the K-edge of barium (37.441 keV), for collecting both 'above' and 'below' the K-edge data sets in a single scan. Results: The SKES has a very good focal size, thus limits the 'crossover' and motion artifacts. In juvenile rats, barium was mostly incorporated in the areas of high bone turnover such as at the growth plate and the trabecular surfaces, but also in the cortical bone as the animals were growing at the time of tracer administration. However, the adults incorporated approximately half the concentration and mainly in the areas where bone remodeling was predominant and occasionally in the periosteal and endosteal layers of the diaphyseal cortical bone. Conclusions: The presented methodology is simple to implement and provides both structural and functional information, after labeling with barium, on bone micro-architecture and thus has great potential for in vivo imaging of pre-clinical animal models of musculoskeletal diseases to better understand their mechanisms and to evaluate the efficacy of pharmaceuticals.